CULTURAL GLOBALIZATION TODAY: KEY TRENDS - Фабрика, А. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article describes and analyzes the main trends of cultural globalization since the intensification of the process to the present day. Also it marked mostly Americanized nature of today's global culture, and there are four areas determining its influence on the culture of individual countries, which are included in the orbit of globalization.